2010
DOI: 10.1128/mcb.00582-09
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of HIC1 Target Genes by CtBP and NuRD, via an Acetylation/SUMOylation Switch, in Quiescent versus Proliferating Cells

Abstract: The tumor suppressor gene HIC1 encodes a transcriptional repressor involved in regulatory loops modulating P53-dependent and E2F1-dependent cell survival, growth control, and stress responses. Despite its importance, few HIC1 corepressors and target genes have been characterized thus far. Using a yeast two-hybrid approach, we identify MTA1, a subunit of the NuRD complex, as a new HIC1 corepressor. This interaction is regulated by two competitive posttranslational modifications of HIC1 at lysine 314, promotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 72 publications
6
110
0
Order By: Relevance
“…36,37 Further, HIC1 has also been shown to indirectly repress transcription by binding to transcriptional activators and preventing binding to target genes. HIC1 has been shown to interact with and inhibit DNA binding of transcription factors such as T-cell factor-4, b-catenin, and STAT3.…”
Section: Hic1 Is Required To Limit Stat3 Signaling In T H 17 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Further, HIC1 has also been shown to indirectly repress transcription by binding to transcriptional activators and preventing binding to target genes. HIC1 has been shown to interact with and inhibit DNA binding of transcription factors such as T-cell factor-4, b-catenin, and STAT3.…”
Section: Hic1 Is Required To Limit Stat3 Signaling In T H 17 Cellsmentioning
confidence: 99%
“…44,45 HIC1 has been shown to interact with and regulate key transcription factors involved in cell cycle progression and cellular metabolism. 37,46 For example, HIC1 is involved in a regulatory feed back loop with the deacteylase SIRT1, 17 which is a key regulator of fattyacid oxidation. 47 Further, it has been demonstrated that fattyacid metabolism is key to memory T-cell development and survival.…”
Section: Hic1 Is Required To Limit Stat3 Signaling In T H 17 Cellsmentioning
confidence: 99%
“…Western blotting was performed as previously described (8). Results are representative of at least two experiments.…”
Section: Methodsmentioning
confidence: 99%
“…HIC1 is able to recruit different co-repressor complexes to its target genes, using short motifs in its central region notably CtBP through a GLDLSKK motif (7), and MTA1, a component of the NuRD complex, through a SUMOylation-dependent ⌿KXEP motif (8). HIC1 also recruits BRG1-ARID1A containing SWI/SNF complexes (9).…”
Section: Hic1 (Hypermethylated In Cancer 1)mentioning
confidence: 99%
See 1 more Smart Citation